Ileal Bile Acid Transporter Inhibition for the Treatment of Chronic Constipation, Cholestatic Pruritus, and NASH - Al-Dury, Samer; Marschall, Hanns-Ulrich (Frontiers in Pharmacology, 2018)
Bile acids are synthesized from cholesterol in the liver, excreted with bile into the duodenum, almost completely taken up again in the distal ileum and finally returned to the liver with portal blood in a process termed enterohepatic circulation. Bile acid synthesis, excretion and reuptake are tightly regulated. The apical sodium-dependent bile acid transporter (ASBT; also known as ileal bile acid transporter (IBAT) and SLC10A2) is pivotal for the almost complete reabsorption of conjugated bile acids in the ileum. Dysfunctional IBAT may be the cause of bile acid diarrhea. Pharmacological IBAT inhibition results in an increased bile acid load in the colon and subsequently a lower bile acid pool, which is associated with improved liver histology in animal models of cholestatic liver disease and non-alcoholic steatohepatitis (NASH). In humans, IBAT inhibitors have been tested in clinical trials with widely different indications: In patients with idiopathic chronic constipation, an increased number of bowel movements was observed. In adult and pediatric cholestatic liver diseases with pruritus, various IBAT inhibitors showed potential to improve itching. Adverse events of IBAT inhibitors, based on their mode of action, are abdominal pain and diarrhea which might patients to withdraw from study medications. So far, no data are available of a study of IBAT inhibitors in patients with NASH. In this review we summarize the preclinical and most recent clinical studies with various IBAT inhibitors and discuss the difficulties that should be addressed in future studies.